Assessment of Screening, Brief Intervention, and Referral to Treatment Training to Interprofessional Health-Care Students - Helen C. Pervanas PharmD; Eric Landry PharmD; Douglas R. Southard PhD; Pamela P. DiNapoli PhD; Paula Smith EdD; Jennifer Towle PharmD; Kate Semple Barta; Kristina Fjeld-Sparks MPH; Devona Stalnaker-Shofner EdD, LPC, NCC (SAGE Publishing, 2019)
Substance abuse and addiction are responsible for an assortment of health and financial concerns in the United States. Tools to identify and assist at-risk persons before they develop a substance use disorder are necessary. Screening, brief intervention, and referral to treatment (SBIRT) can be utilized by health-care professionals to identify those at risk to minimize health-related complications and the potential of developing a substance use disorder. The primary objective of this study was to provide educational training sessions on SBIRT to health-care students utilizing interprofessional education activities and assess perceptions of the training sessions and activities with regard to confidence to utilize SBIRT in at-risk patients and overall student satisfaction with SBIRT instruction. The research protocol enrolled students of pharmacy, nursing, medicine, behavioral health, and physician assistant studies who received interprofessional SBIRT training. Students completed an anonymous posttraining online survey, measuring student perceptions of knowledge gained and confidence to utilize training. A total of 303 students completed the SBIRT training. Approximately 70% of students were satisfied with the training materials, instruction, quality, and experience. After training, 78% were confident that they could perform screening for substance abuse, conduct a brief intervention (80%), and when to refer to treatment (71%). A total 73% of students reported that the asynchronous online-based activity was extremely effective in increasing knowledge of the roles and responsibilities of other disciplines and providing opportunities to interact with students from other health professions. Interprofessional education-trained students from multiple health-care disciplines feel comfortable performing SBIRT to identify persons at risk for substance misuse in practice.